Skilled Regulatory Affairs Professional with a Focus on Global Compliance and CMC - Ramya Moparthi (The Bioscan, 2023)
Regulatory affairs professionals with expertise in global compliance and Chemistry, Manufacturing, and Controls (CMC) play a vital role in ensuring that pharmaceutical products meet the stringent regulatory requirements set by authorities worldwide. These professionals manage regulatory submissions, ensure compliance with local and international guidelines, and oversee the quality, safety, and efficacy of products throughout their lifecycle. This article explores the role of regulatory affairs professionals who specialize in global compliance and CMC, examining their key responsibilities, the challenges they face in a dynamic regulatory environment, and their impact on the pharmaceutical industry. The paper also highlights the importance of harmonization efforts, emerging trends in CMC regulations, and strategies for navigating complex global regulatory frameworks.